Marxism and science fiction - Alfaro Vargas, Roy (2016)
This article analyzes the relation between Marxism and science fiction around the con- cept of novum and the process of cognitive estrangement, which define science fiction. This article studies the theory and practice of science fiction, so long as science fiction is a manifestation of the critical theory and, therefore, as a part of an ontology of congruence and of the social critique. Also, it is established a critique of the current science fiction what is linked to Neoliberalism and to the pedagogical project of World Bank.